TANTANGAN DAN INOVASI MANAJEMEN PENDIDIKAN MULTIBUDAYA DI ERA GLOBAL - M Hafiz Nashrullah; Akil Akil; Taufik Mustofa (Jurnal Manajemen Pendidikan, 2026)
The development of globalization has had a significant impact on the world of education, particularly in the context of multicultural education management. Indonesia, as a nation rich in ethnic, linguistic, and religious diversity, faces major challenges in creating an inclusive and adaptive education system that embraces cultural differences. The background of this study arises from the need to understand how educational institutions can manage diversity not as a source of conflict but as a strength in building a tolerant and globally competitive national character. The purpose of this research is to identify the challenges faced by multicultural education management in the global era and to explore various innovations implemented to address these issues. The method used in this study is qualitative research through literature analysis and secondary data from relevant scholarly sources. The results indicate that the main challenges include the low cultural competence of educators, the lack of multicultural-oriented curricula, and the limited educational policies that are responsive to diversity. The innovations identified include the implementation of curricula based on multicultural values, global-minded teacher training, the use of cross-cultural educational technology, and the strengthening of collaboration among school communities.